Moskwa w bieli i czerni - trzy filmowe portrety miasta - Czaja, Justyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
Moscow in black and white - three film portraits of the city This article presents the three different portraits of Moscow depicted in the Russian films Walking the Streets of Moscow by Georgy Danielija, Taxi Blues by Pavel Lungin and Moscow by Alexander Zeldovich. The times the films were made (the thaw period, the period after the collapse of theSoviet Union, and the decline during the 1990s) determine differences in the directors’ perceptions. The picture of the city becomes a reflection of both hope and of more contemporary fears and anxieties.